Unlocking the mechanical, thermodynamic and thermoelectric properties of NaSbS2: A DFT scheme - M.N.H. Liton; A.K.M. Farid Ul Islam; M.S.I. Sarker; M.M. Rahman; M.K.R. Khan (Heliyon)
The present study focuses on the ground state mechanical, acoustic, thermodynamic and electronic transport properties of NaSbS2 polymorphs using the density functional theory (DFT) and semi-classical Boltzmann transport theory. The mechanical stability of the polymorphs is affirmed by the calculated elastic tensor. The calculated elastic properties asserted that all the polymorphs exhibit soft, brittle, anisotropic nature containing dominant covalent bonding. The 2D polar graphs are used to describe the anisotropic characteristic of the elastic parameters. The estimated value of Young's modulus and lattice thermal conductivity suggested that the polymorphs could be suitable for thermal barrier coating. Heat capacity, melting temperature, thermal conductivities, Grüneisen parameter, and thermal expansion coefficient of the polymorphs have also been studied to demonstrate thermodynamic behavior. The predicted lower values of lattice thermal conductivity declared that NaSbS2 polymorphs exhibit excellent electrical conductivity and transport properties. The estimated Seebeck coefficient (S), power factor (PF) and figure of merit (ZT) suggested that n-type triclinic and monoclinic, as well as p-type trigonal NaSbS2, are better for thermoelectric applications. The optimal carrier concentration for monoclinic structure is 1021 cm−3 for T < 750 K, while it becomes 1020 cm−3 for T > 750 K. It is also found that the optimal carrier concentration of the trigonal is 1021 cm−3, whereas it is 1020 cm−3 for triclinic structures. Therefore, it can be stated that NaSbS2 polymorphs possess excellent thermoelectric features, making them a promising choice for thermoelectric (TE) applications.